Are institutional investors subject to gambling preference? Evidence from detailed investor bids of IPO auctions in China. Issue 4 (4th July 2022) - Shen, Haomin; Cheng, Xiaoke; Han, Lin; Chan, Kam C.
ABSTRACT: Using a unique disclosure database of institutional investor bidding information in Chinese initial public offerings (IPOs), we examine the preference for lottery-like IPO shares of institutional investors. We document that IPOs with higher expected skewness have higher institutional bidding prices and higher offline oversubscription ratio. The effect is stronger for sub-samples with higher investor sentiment and IPOs with higher valuation uncertainty. Moreover, higher expected skewed IPOs experience higher issue prices and initial returns but lower long run returns. These results show that institutional investors have gambling preference for IPO investments and the expected skewness of returns explain institutional bidding prices.